Exploring the key genetic association between chronic pancreatitis and pancreatic ductal adenocarcinoma through integrated bioinformatics - Guo, Kai; Zhao, Yatong; Cao, Yingying; Li, Yuan; Yang, Meng; Tian, Ying; Dai, Jianmeng; Song, Lina; Ren, Shuai; Wang, Zhongqiu (Frontiers in Genetics, 2023)
Background: Pancreatic ductal adenocarcinoma (PDAC) develops rapidly and has a poor prognosis. It has been demonstrated that PDAC and chronic pancreatitis (CP) have a close connection. However, the underlying mechanisms for CP transforming into PDAC are still unclear. The purpose of this study was to investigate the real hub gene and signatures in the development of CP and PDAC. Methods: RNA-seq data of CP and PDAC were downloaded from the Gene Expression Omnibus (GEO) database. Weighted gene co-expression network analysis (WGCNA) was performed to construct a gene co-expression network between CP and PDAC. GEO2R and a Venn diagram were used to identify differentially expressed genes. Then visualized networks were constructed with ClueGO, and modules of PPI network were calculated by MCODE plugin. Further validation of the results was carried out in two additional cohorts. Analyses of CEL-coexpressed genes and regulators including miRNAs and transcription factors were performed by using the corresponding online web tool. Finally, the influence of CEL in the tumor immune microenvironment (TIME) was assessed by immune contextual analysis. Results: With the help of WGCNA and GEO2R, four co-expression modules and six hub genes were identified, respectively. ClueGO enrichment analysis and MCODE cluster analysis revealed that the dysfunctional transport of nutrients and trace elements might contribute to CP and PDAC development. As a result of the validation test, the real hub gene CEL was identified with a markedly low expression in PDAC. According to the miRNA-gene network construction, hsa-miR-198 may be the key miRNA. A strong correlation exists between CEL and TIME after an evaluation of the influence of CEL in TIME. Conclusion: Our study revealed the dysfunctional transport of nutrients and trace elements may be common pathogenesis of PDAC and CP. Examination on these common pathways and real hub genes may shed light on the underlying mechanism.